Book reviews: Governance in South, Southeast and East Asia: Trends, issues and challenges. Edited by Ishtiaq Jamil, Salahuddin M. Aminuzzaman, and Sk. Tawfique M. Haque. London: Springer, 2015, pp. 285, ISBN: 978-3-319-15218-9 - Jamaiudin, Norhaslinda (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This book offers a comparative analysis on governance in South, Southeast, and East Asian countries. It provides extensive conceptual, theoretical, and empirical discussions on governance with rigorous comparative studies of how governance is practised in different countries across those contexts. The authors present broad analyses on the discrepancies of governance reforms on the basis of real and practical problems and examine the factors that drive and challenge governance based administrations. The tune of the book is to measure the impact of governance on public management reforms, country developments, and economic growths. The by-product of the adoption of the governance model is thoroughly analysed. The book is divided into 15 chapters, opening with a conceptual discussion on governance. The chapter is completed with arguments on the relevance of the governance model in South Asia and beyond. Descriptive, explanatory, and exploratory analyses are presented using reliable primary and secondary data with sound methodological foundations.